Ron Arad no discipline - Arad, Ron 1951; Antonelli,Paola (Museum of Modern Art Distributed by D.A.P., 2009)
"Published to accompany the first major retrospective of Arad's work in the U.S., this volume features an interview with the artist and essays on his use of innovative materials and technology, his role as an educator and communicator on the importance of design and his place in the world of design and the larger art market. A lavishly illustrated plate section provides visual and written documentation of approximately 80 works"--Provided by publisher.